DEPTH DISTRIBUTIONS OF RBE-WEIGHTED DOSE and PHOTON-ISOEFFECTIVE DOSE FOR BORON NEUTRON CAPTURE THERAPY. Issue 1 (11th December 2018) - Sato, Tatsuhiko; Masunaga, Shin-ichiro; Kumada, Hiroaki; Hamada, Nobuyuki
Abstract: Two types of dose were proposed for use in the treatment planning of boron neutron capture therapy (BNCT) for expressing its high relative biological effectiveness (RBE). On one hand, the RBE-weighted dose is the sum of the absorbed doses weighted by fixed RBE for each dose component of BNCT. On the other hand, photon-isoeffective dose is the photon dose to give the same biological effect calculated considering the dose dependence of RBE and the synergetic effect between different types of radiation. In this study, the depth distributions of the two types of dose in a phantom placed at an accelerator-based BNCT field were calculated using Particle and Heavy Ion Transport code System, PHITS, coupled with an extended stochastic microdosimetric kinetic model. Compared with the corresponding RBE-weighted dose, the calculated photon-isoeffective dose was larger at lower absorbed dose and was smaller at higher absorbed dose, primarily due to the consideration of the dose dependence of RBE. In addition, our calculation revealed that the large variance of the intercellular 10 B concentration greatly reduces the photon-isoeffective doses. These results suggest that the considerations of the dose dependence of RBE as well as the intercellular heterogeneity in 10 B distribution are indispensable for the precise estimate of the biological effect of BNCT.